Income dynamics in three societies: an investigation of social dynamics using old and new types of social indicators - Zsolt Spéder; Roland Habich (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
This paper* sets out to offer new insight into social change, especially social transformation. The authors have drawn up new types of social indicators to encapsulate the nature of social change, with the intention of widening its meaning. The investigation draws on longitudinal panel studies: the German Socio-Economic Panel Study 1990–96 (GSOEP) and the Hungarian Household Panel 1992–96 (HHP). The single, albeit crucial social dimension examined is the income position of families, including the mobility of families within the income structure. The analysis takes a comparative and a longitudinal approach. Hungary and East Germany, as societies in transition, are compared with West Germany, as a case of `usual' social change, while the income mobility of individuals is traced over time. Both these aspects are examined in relation to modernization theories. While classical measures such as the Gini Coefficient show a remarkable stability of income inequality, the indicators elaborated here reveal a high degree of individual movement behind the macro stability.
Keywords: 300; Einkommensverteilung; Haushaltseinkommen; Soziale Mobilität; Neue Bundesländer; Ungarn; Alte Bundeslände